César Moro: Hybrid And T ransnational Poet - Westphalen Rodríguez, Yolanda (2017)
Euphony, that pleasing sonority that results from the correct combination of the acoustic elements of the words, is a decisive component of Moro's poetry and key in the choice of French as his language of writing. Thus, the paper will address three aspects of the problem of the use of language in César Moro's work. First, his definition as a bilingual writer of French-expression; Secondly, its adoption of French as part of a surrealist transnationalism; And, last, the characteristics of his Francophone intercultural hybridism that led him to build his own poetic and cultural diglossia.